Overview of Dietary Quality in Adolescents at State Junior High School 4 Depok, Sleman Regency, Yogyakarta - Wardani, Desy Fitria; Prasetyaningrum, Yunita Indah; Kadaryati, Sri; Wulan, Yuni Kartika (Universitas Al Azhar Indonesia, 2023)
Adolescents are categorized into nutritionally vulnerable age. Dietary quality is one factors that influence nutritional status in adolescents. Poor dietary quality will have impact on development that is not optimal and more susceptible to non-communicable diseases, such as obesity and diabetes melitus. This study aims to describe dietary quality of adolescents at Junior High School 4 Depok, Sleman, Yogyakarta. This was descriptive quantitative observational study with cross-sectional design. The study site was state junior high school 4 Depok, Sleman, Yogyakarta, which is located in obesogenic sub-urban area, on May–June 2023.The were 90 respondents of Junior High School students in 7th and 8th grades, who were determined using purposive sampling. The instrument used Dietary Quality Index for Adolescents (DQI-A) form and 24-hour recall form. The results showed that mostly adolescents had poor dietary quality category (80%). The results of Dietary Quality (DQ) category were 44.77% and 56.69%, Dietary Diversity (DD) category were 66.67% and 55.56%, Dietary Equilibrium (DE) category were 29.97% and 24.27% (respectively in weekday and weekend). The final DQI-A score showed that average weekdays were 45.17% and median weekends were 46.71%. In conclusion, adolescents at state junior high school 4 Depok Sleman Yogyakarta mostly has a poor category.Keywords: Dietary Quality, Adolescents, and School Children